Olivia Holm-Møller en kunstnerkreds omkring 1900-1930 : Carla Colsmann, Bizzie Høyer, Sophie Pedersen, Marie Graae, Elise Konstantin-Hansen - Pedersen, Teresa Østergaard 1981-; Mogensen Bech, Inge Lise 1974-; Angkær Jørgensen, Ulla 1963-; Nygaard, Pernille Zidore 1987- (Holstebro Kunstmuseum, 2022)
'I have done as well as I could, but I am very concerned when I see the names on the Censorship, I will probably get them discarded. They also submit, right? It is now no fun to send to Charlottenborg again. We should much rather look at getting together for an exhibition again sometime, that is the only satisfactory way to exhibit.' Olivia Holm-Møller to Carla Colsmann on 18 February 1918. The quote above is from a letter, Olivia Holm-Møller (1875-1970) writes to fellow artist Carla Colsmann (1887-1974). She expresses her frustration with the censored exhibitions of the time and encourages Colsmann for another joint exhibition, which is described as the only satisfactory alternative. 'Olivia Holm-Møller: a circle of artists around 1900-1930' is about this previously undescribed exhibition community in Danish art history. Exhibition: Holstesbro Kunstmuseum, Denmark (17.09.2022 - 22.01.2023)
Impressum: "Olivia Holm-Møller - en kunstnerkreds omkring 1900-1930, Holstebro Kunstmuseum, 17. september 2022-22. januar 2023"
Limited edition of 400 copies
Keywords: Holm-Møller, Olivia -- 1875-1970; Geschichte 1900-1930; Künstlerin; Kunstbetrieb; Dänemark; Holm-Møller, Olivia / 1875-1970 / Exhibitions; Holm-Møller, Olivia - 1875-1970 / (OCoLC)fst00390260; 1900-1999; Women artists / Denmark / Exhibitions; Art, Danish / 20th century / Exhibitions; Art, Danish - Exhibitions / (OCoLC)fst00816176; Women artists / (OCoLC)fst01177159; Exhibition catalogs / (OCoLC)fst01424028; Ausstellungskatalog -- Holstebro Kunstmuseum -- 17.09.2022-22.01.2023 -- Holstebro; Bildband